Influence of the heavy fuel spill from the Prestige tanker wreckage in the overlying seawater column levels of copper, nickel and vanadium (NE Atlantic ocean) - Santos-Echeandía, Juan; Prego, R.; Cobelo-García, A. (Journal of Marine Systems, 2008)
8 pages, 5 figures, 3 tables The water column above the Prestige wreckage was sampled during two consecutive campaigns: Prestinaut (December 2002) two weeks after the tanker sunk and HidroPrestige0303 (March 2003) one month after the sealing of the main fuel leaks. Samples of the original cargo fuel and the emulsified fuel in the surface of the ocean were also collected. Analysis of the fuel indicated the release of 135 kg of Cu, 1700 kg of Ni and 5300 kg of V from the original fuel to the water column, remaining 35 kg of Cu, 3100 kg of Ni and 13,800 kg of V in the emulsified fuel. The metal partitioning between the water column and the emulsioned floating fuel, Cu > Ni ~ V, are in accordance with the stability index for the metal–nitrogen bond in metalloporphyrins. This release had an impact on dissolved trace metal concentrations in the water column. An increase on dissolved copper (2.8–4.7 nM) and nickel (2.2–8.0 nM) with respect to natural values (1–3 nM for Cu and 1.6–5 nM for Ni) was observed. Values for vanadium (28–35 nM) were in the range of pristine North Atlantic waters (30–36 nM). This contamination was especially observed in the upper water column (0–50 m), associated with the mixing of seawater with the fuel moving upwards, and in deep waters, where the residence time of fuel is higher. Future research in this field should focus on the environmental variables and the processes that control the release of contaminants from fuels for a better assessment of the contamination in oil-spill events J. Santos-Echeandía thanks the Basque Government for financial support (pre-doctoral grant). This communication is a contribution of the Spanish CICYT coordinate project “Biogeochemical budget and modelling of heavy metal fluxes in a Galician ria (METRIA)”, ref. REN2003-04106-C03 Peer reviewed